Comparison of Metolazone Versus Chlorothiazide in Acute Decompensated Heart Failure with Diuretic Resistance. Issue 2 (April 2015) - Moranville, Michael P.; Choi, Suji; Hogg, Jennifer; Anderson, Allen S.; Rich, Jonathan D.
Summary: Aims: Sequential nephron blockade with thiazide‐like diuretics is a strategy used to overcome diuretic resistance in acute decompensated heart failure (ADHF), but head‐to‐head studies are lacking and equipoise exists regarding the preferred thiazide‐like diuretic in this setting. We thus compared the effectiveness of oral metolazone versus intravenous (IV) chlorothiazide as add‐on therapy to loop diuretics in hospitalized patients with ADHF and renal dysfunction. Methods: This retrospective cohort study evaluated the efficacy and safety of oral metolazone versus IV chlorothiazide as add‐on therapy to loop diuretics in patients hospitalized with ADHF and renal dysfunction. The primary endpoint was net urine output (UOP) at 72 h after initiation of thiazide‐like diuretics. Safety endpoints included worsening renal function, hypotension, and electrolyte abnormalities. Results: Fifty‐five patients were enrolled with 33 patients receiving metolazone and 22 patients receiving chlorothiazide. There was no difference in median net UOP at 72 h in those receiving metolazone (4828 mL, interquartile range [IQR] 2800–7209 mL) compared to chlorothiazide (3779 mL, IQR 1885–6535 mL) ( P = 0.16). There was no difference in hypotension, worsening renal function, hyponatremia, or hypokalemia ( P = NS for all comparisons). Hospital length of stay was shorter in the metolazone cohort (median 7 days) compared to chlorothiazide (median 15 days), suggesting the chlorothiazide cohort was likely sicker. Conclusion: Sequential nephron blockade with either metolazone or chlorothiazide appears to be efficacious and safe in ADHF, renal dysfunction, and diuretic resistance. Given the considerable cost difference favoring oral metolazone, larger randomized studies are warranted to confirm our findings and to exclude the possibility of confounding by indication.